The foundation of ethical and moral dimensions for Indonesian future - Winanti, Ni Putu; Widyastuti, Ni Putu (Institute for Advanced Science Social, and Sustainable Future, 2024)
The basic concept of ethics and morality expressed by humans actually originates from the teachings of religion (theology) that view humans as creations of the divine, originating from what is holy. However, the issue of corruption and various forms of ethical and moral violations within the nation pose a significant threat that can destroy the pillars of national integrity in Indonesia, and this must be acknowledged by all Indonesians in order to find solutions to resolve and overcome it. This article is the result of qualitative research that examines the establishment of the ethical and moral dimensions for the future of the Indonesian nation. The data in this research was obtained through a study of literature related to the research theme and analyzed using content analysis. One way to build and maintain the ethics and morality of the Indonesian nation is by developing multicultural education. This will instill nationalism, patriotism, respect for human rights, and democratization. It is crucial to implement this in Indonesia immediately to prevent religious, ethnic, racial, and intergroup conflicts. To prevent various potential conflicts and future terrorism, multicultural education can be implemented starting from the family environment, schools, and society. In this regard, education largely depends on the exemplary behavior of parents at home, teachers at school, religious leaders, and community leaders in their respective communities. This begins with revising the curriculum and teaching materials, ensuring the availability of adequate teaching materials, and enhancing the ability of teachers and lecturers to understand multicultural education.